Becoming a mother of a premature baby in the context of the pandemic: a place of dual helplessness - Carolina Marocco Esteves; Adrielly Alves; Mariane Svirski; Cesar Augusto Piccinini (Estudos de Psicologia (Campinas))
Abstract Objective The study aimed to investigate women’s maternal experience in response to the premature birth of their babies during the pandemic. Method A multiple case study design was used, with the participation of six women residing in different cities in Brazil. An inductive thematic analysis of the interviews was adopted. Results Factors related to the pandemic, such as social isolation, vaccination, fake news, and the risk of preterm birth, accentuated women’s feelings of loneliness. Work overload was identified as a stress factor among the participants that may have contributed to premature birth. The intermittent threat of virus contamination triggered signal anxiety, resulting in a dual sense of helplessness for these women. The relationship with the care network was ambiguous and deficient; however, when effective, it was experienced as emotional support and significantly reduced the feeling of helplessness. Conclusion The results provide insights for the development of clinical approaches by revealing that women were exposed to illness-inducing factors that intensified their psychological strain due to confinement and prematurity.